Molecular and supramolecular chemistry of mono- and di-selenium analogues of metal dithiocarbamates - Lee, See Mun *; Heard, Peter *; Tiekink, Edward R. T. * (Elsevier, 2018)
This bibliographic review summarises the coordination chemistry of mono- and diselenium analogues of metal dithiocarbamate ligands, [RRꞌNCS2]-, as revealed by X-ray crystallography and spectroscopy (77Se NMR and infrared). The Se-ligands are usually chelating but, bridging modes, up to 4, are known. Reflecting the larger size, greater polarisability and presence of a polar-cap (-hole), selenium atoms are more likely to be involved in secondary-bonding (chalcogen-bonding) than sulphur when a competition exists. Isostructural relationships are established across the series in about one-third of the structures.